Diversity and distribution of Ludwigia (Onagraceae) in Paraíba State, Northeastern Brazil - Rocha, Amanda Macêdo; de Melo, José Iranildo Miranda (European Journal of Taxonomy, 2020)
This paper provides a taxonomic assessment and distribution details of the species of the genus Ludwigia L. (Onagraceae) for the Paraíba State, Northeastern Brazil. Six species were found: L. erecta (L.) H.Hara, L. helminthorrhiza (Mart.) H.Hara, L. hyssopifolia (G.Don) Exell, L. leptocarpa (Nutt.) H.Hara, L. nervosa (Poir.) H.Hara and L. octovalvis (Jacq.) P.H.Raven. Ludwigia nervosa was recorded for the first time in the studied area. Our taxonomic treatment comprises an identification key to the species. For each species, description, illustrations, taxonomic comments, flowering and fruiting data, geographic distribution map, and the conservation status for the studied area are provided. Among the recorded species, three were classified as “Near Threatened”, two as “Vulnerable” and one as “Critically Endangered”.